"Since \\ we \\ have \\\\\n2x_1 + x_2 + x_3 + x_4 = 6\\\\\n\n3x_1 + 2x_2 + x_3 + 2x_4 = 8\\\\\nThis \\ system \\ can \\ written\\ in \\ the \\ form\\\\\n\\begin{bmatrix}\n 2 & 1&1&1\\\\\n 3&2&1&2\n\\end{bmatrix}\n\\begin{bmatrix}\n x_1\\\\x_2\\\\x_3\\\\x_4\n\\end{bmatrix}=\\begin{bmatrix}\n 6\\\\\n 8\n\\end{bmatrix}\\\\\n\\text{Using Gauss elimination, we get }\\\\\n\\begin{bmatrix}\n \\begin{array}{cccc|c}\n 2 & 1 &1&1&6 \\\\ \n 3& 2 & 1&2&8 \\\\\n \\end{array}\n\\end{bmatrix}\n\\xrightarrow {R_2-R_1\\rightarrow R_2}\\\\ \\\\\n\\\\\n\\begin{bmatrix}\n \\begin{array}{cccc|c}\n 2 & 1 &1&1&6 \\\\ \n 0& -1 &0&1&2 \\\\\n \\end{array}\n\\end{bmatrix}\\xrightarrow {-R_2\\rightarrow R_2}\\\\ \\\\\n\\\\\n\\begin{bmatrix}\n \\begin{array}{cccc|c}\n 3 & 1 &1&1&6 \\\\ \n 0& 1 &0&-1&-2 \\\\\n \\end{array}\n\\end{bmatrix}\\\\\n\\text{So, we get the rank of matrix is 2}\\\\ \\text{ and the number of unknowns is 4}\\\\\n\\text {this implies , we have 2 free unknown}\\\\\n\\text{So, let}\\\\\nx_3=t , x_4=s.\\\\\n\\text{Now, we have}\\\\\nx_2-x_4=4\\Rightarrow x_2=4-s\\\\\n2x_1 + x_2 + x_3 + x_4 = 6\\\\\n\\Rightarrow 2x_1 =- x_2 - t -s+ 6\\\\\n2x_1 =-4+s - t -s+ 6\\\\\n2x_1 =2-t\\\\"
Comments
Leave a comment